Kazimierz Wielki jako reformator i człowiek - Skodlarski, Janusz (Annales. Etyka w Życiu Gospodarczym, 2008)
Endowed with all the traits of an outstanding monarch and creator of his state, King Kazimierz III(also known as the Great) appears one of the greatest figures in the history of Poland. It was him wholaid out the legal and political foundation of the modern state. He initiated legislative, administrative,economic, military and cultural reforms which became the source of the power of the Jagielloniandynasty.However, apart from the above mentioned virtues, Kazimierz Wielki had a number of vicesand weaknesses. He tended to be irritable and bad-tempered. He overly appreciated jewels and luxury.What is more, he was promiscuous and overindulged in drinking and eating.